Pathological Impact of Methotrexate on Body Weight, Absolute and Relative Weight of Liver with Amelioration by Sulforaphane in Albino Rats - Sadia Sundus, Kaneez Fatima, Talat Samreen, Asma Aijaz, Erum Khan, Khalida Anwar, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the changes in Body Weight, Absolute and Relative weight of Liver in methotrexate impaired liver with amendment by sulforaphane. Design of research: Experimental. Abode and Period of study: Research was conducted in BMSI, Karachi &duration was ten days. Materials and Methods: For experiment Forty young albino rats of 3-4months old of 200-300gm were taken, Primarily period of study was 20 days however during the pilot study, rats started dying after 10 days, so the duration was reduced to 10 days for final study. Rats were alienated into 4 sets, A was control group, B set was given Inj Methotrexate intraperitoneally. C set was given Inj Methotrexate intraperitoneally along with sulforaphane by N/G tube. D set was given only sulforaphane by N/G tube. After the completion of study, rats were dissected and liver was removed from abdominal cavity of rats and absolute weight of liver was weighed on Sartorius balance. The relative weight of the liver was calculated with the help of formula. Mean weight of liver (G) The relative weight of liver = X100 Final weight of the animal Results: B group showed remarkable decrease in the body weight while absolute liver weight & relative liver weight is increased however group C had slight reduction in the body weight while absolute liver weight & relative liver weight is slightly increased. Conclusion: This study accomplishes that sulforaphane amended the detrimental effects of methotrexate. Keywords: sulforaphane, methotrexate, superoxide dismutase (SOD), dihydrofolate reductase enzyme (DHFR), nuclear factor erythroid-derived 2(Nrf2), Tetrahydrofolate (THF)